Distribution of gas phase polycyclic aromatic hydrocarbons (PAHs) in selected indoor and outdoor air samples of Malaysia: a case study in Serdang, Selangor and Bachang, Malacca - Abd Hamid, Haris Hafizal; Lim, Wan Wan; Phang, Ignatius Ren Kai; Latif, Mohd Talib; Kannan, Narayanan (Thai Society of Higher Education Institutes on Environment, 2017)
Distribution of 10 polycyclic aromatic hydrocarbons (PAHs) in the gas phase of air from selected indoor and outdoor areas of Selangor and Malacca, Malaysia has been investigated. A locally designed Semi Permeable Membrane Device (SPMD) was applied for passive air sampling for 37 days at selected locations. Cleanup was carried out with Gas Purge - Micro Syringe Extraction (GP-MSE) and the final analysis was using Gas Chromatography-Mass Spectrometry (GC-MS). In this study, 6 indoor and 12 outdoor locations were selected for air sampling. A total of 10 compounds of PAHs (Ʃ10PAHs) were determined in the range of 0.218 ng/m3 - 1.692 ng/m3 and 0.378 ng/m3 - 1.492 ng/m3 in outdoor and indoor samples respectively. In the outdoor samples, locations such as near a petrol station and heavy traffic showed the maximum levels of Ʃ10PAHs, while rooftop samples showed the lowest Ʃ10PAHs. The distribution of gas phase Ʃ10PAHs was influenced by vehicular emission. Low molecular weight (LMW) compounds (2-3 rings) were dominant in all samples (>70%) indicating that SPMD has successfully sampled the gas phase of the air.